THE PREVENTION OF NEGATIVE CONTENT BY USING VPN (VIRTUAL PRIVATE NETWORK) TOWARDS WEBSITE THAT IS BLOCKED BY THE GOVERNMENT - Nugroho, Wahyu; Ismunarno, Ismunarno; Setyanto, Budi (Universitas Negeri Semarang (UNNES), 2019)
This research aims to know how is the prevention of negative content that is accessed by using VPN towards website that is blocked by the government through Indonesian National Police and the obstacle of its prevention. The research conducted is non-doctrinal research, which is a research to know some practical situations. This research uses primary and secondary data. Primary data is direct interviews with the Indonesian National Police and Ministry of Communication and Informatics to know blocking efforts and regulations of applications missuse. Secondary data is obtained by literature studies. The government has blocked websites with negative content based on Minister of Communication and Informatics Regulations Article 19 years of 2014 about Handling of Websites with Negative Content. Government-blocked websites can be opened with VPNÂ applications. Indonesian National Policeâ€™s step in handling the missuse of VPN applications to access negative content is with the prevention efforts. There is no device missuse regulations yet makes an obstacle to prevent represively. Ministry of Communication and Informatics begins to regulate the utilization of VPN application in the terms of licensing.